2010
DOI: 10.1093/sleep/33.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Nonrestorative Sleep as a Distinct Component of Insomnia

Abstract: This study confirms that NRS can occur independently of other components of insomnia. Daytime symptoms were as severe in individuals with NRS-only as those whose NRS symptoms were combined with DIS or DMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 11 publications
1
54
0
1
Order By: Relevance
“…In primary insomnia, the disorder has an unknown physical, mental or environmental cause (APA, 2008; WHO, 2008). Non‐restorative sleep (subjectively perceived poor sleep quality) is a distinct pathology which might occur independently of difficulties falling asleep or poor sleep maintenance (Roth et al, 2010). Daytime impairment in insomnia may include, but is not limited to, problems such as fatigue, memory impairment, mood disturbances, proneness for errors, tension headaches and gastrointestinal symptoms in response to sleep loss (Edinger et al, 2004).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…In primary insomnia, the disorder has an unknown physical, mental or environmental cause (APA, 2008; WHO, 2008). Non‐restorative sleep (subjectively perceived poor sleep quality) is a distinct pathology which might occur independently of difficulties falling asleep or poor sleep maintenance (Roth et al, 2010). Daytime impairment in insomnia may include, but is not limited to, problems such as fatigue, memory impairment, mood disturbances, proneness for errors, tension headaches and gastrointestinal symptoms in response to sleep loss (Edinger et al, 2004).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…Subjective sleep quality is also central to complaints of non-restorative sleep, which was included as a subtype of insomnia until publication in the DSM-5. Research by Roth and colleagues has shown that complaints of non-restorative sleep are stable and separable from those of difficulty initiating or maintaining sleep, though still associated with comparable levels of functional impairment [3]. In the general population, non-restorative sleep complaints are quite common [4] and associated with a variety of physical and mental conditions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research identifying characteristics of sleep disturbances and the emotional associations of sleep loss is needed and continues to be understudied (Kahn et al, 2013;Ohayon, 2005;Roth et al, 2010;Vernon, Dugar, Revicki, Treglia, & Buysse, 2010;Wilkinson & Shapiro, 2012).…”
mentioning
confidence: 99%